A picture says it all? The validity of photograph coding to assess household food waste. (July 2019) - van Herpen, Erica; van der Lans, Ivo
Highlights: Coding of waste photographs is a promising method to measure household food waste. Coders can accurately assess the weight of food waste from photographs. Correlations between estimated and actual food waste are high. Coders respond to differences in food density and amount. Abstract: Valid measurements are essential in studies into levels of household food waste and differences therein over time, cultures, or consumer groups. They are also key to identifying factors that affect waste levels and to testing the effects of potential interventions. Yet, there is a lack of valid measurement methods for household food waste. The current study assesses the validity of coding of photographs of food waste as a measurement method. In this study, nine coders each estimated 104 food waste instances from photographs, which structurally varied in food amount, food density, size of the container (plate, glass, bowl, pan, etc.) and food category. Comparisons of estimated weights with actual weights show that coders can accurately estimate the weight of food waste from photographs, without general over- or underestimation and with satisfactory correlations with actual weights. Food waste incidences that are more or less difficult to estimate are discussed, as well as differences between coders. Overall, the method appears promising for application in studies examining household food waste levels.